Cardiac electrical conduction, autonomic activity and biomarker release during recovery from prolonged strenuous exercise in trained male cyclists - Stewart, G. M.; Kavanagh, J. J.; Koerbin, G.; Simmonds, M. J.; Sabapathy, S. (European Journal of Applied Physiology, 2014)
Purpose Although markers of myocyte injury, electrolyte disturbances and an autonomic imbalance have been reported following exercise, the effect of prolonged strenuous activity on cardiac electrical conduction is not well understood. This study examined atrial and ventricular conduction dynamics during recovery from exercise. Methods Electrocardiographic intervals were obtained from eight highly-trained males before, during recovery (15, 30, 45 and 60 min post-exercise) and 24 h after a prolonged bout of strenuous exercise. Time-domain, frequency-domain and non-linear analyses of the RR, PR and QT intervals were analysed to investigate the effect of exercise on autonomic modulation and cardiac electrical conduction. Serum electrolyte and high-sensitivity cardiac troponin T (hs-cTnT) concentrations were measured before exercise, and after 60 min and 24 h of recovery. Results The root mean square of the successive differences of RR, PR and QT intervals was significantly reduced during recovery (p < 0.05). Normalised low- and high-frequency power of RR intervals significantly increased and decreased, respectively, during recovery. Approximate entropy of PR and QT intervals, and the QT-variability index significantly increased during recovery. All measures except mean QT interval (pre 422 ± 10 ms vs 24 h post 442 ± 11 ms, p = 0.013) returned to pre-exercise values after 24 h. Serum hs-cTnT was significantly elevated 60 min after exercise (pre 5.2 ± 0.7 ng/L vs 60 min post 27.4 ± 6.2 ng/L, p = 0.01) and correlated with exercising heart rate (R 2 = 0.89, p < 0.001). Serum electrolyte concentrations were unchanged (p > 0.05). Conclusion The results suggest suppressed parasympathetic and/or sustained sympathetic modulation of heart rate during recovery, concomitant with perturbations in atrial and ventricular conduction dynamics. Exercise-induced hs-cTnT release was heart rate dependent.